1984
DOI: 10.1128/mcb.4.9.1843
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specificity of type I collagen gene expression is determined at both transcriptional and post-transcriptional levels.

Abstract: We analyzed the control of type I collagen synthesis in four kinds of differentiated cells from chicken embryos which synthesize very different amounts of the protein. Tendon, skin, and smooth muscle cells were found to have identical amounts of type I collagen RNAs; however, the RNAs had inherently different translatabilities, which were observed both in vivo and in vitro. Chondrocytes also had substantial amounts of type I collagen RNAs, even though they directed no detectable synthesis of the protein either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
1

Year Published

1985
1985
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 34 publications
(39 reference statements)
8
48
1
Order By: Relevance
“…Still the cells synthesized only type I collagen. Our data, in agreement with findings of other groups (12,14,21,23), might suggest a translational regulation of the type I collagen expression during the in vitro differentiation process of chondrocytes from dedifferentiated cells.…”
Section: Discussionsupporting
confidence: 93%
“…Still the cells synthesized only type I collagen. Our data, in agreement with findings of other groups (12,14,21,23), might suggest a translational regulation of the type I collagen expression during the in vitro differentiation process of chondrocytes from dedifferentiated cells.…”
Section: Discussionsupporting
confidence: 93%
“…An unexpected finding of considerable interest was the presence of low levels of type II collagen mRNA in the cytoplasm of prechondrogenic mesenchymal cells at the earliest stages of limb development, indicating the type II collagen gene is being transcribed well before the onset of overt cartilage differentiation and the accumulation of detectable amounts of type II collagen. Furthermore, our results are consistent with other recent studies (1,9,31) indicating that type I collagen gene expression during chondrogenesis is regulated, at least in part, at the translational level, since substantial amounts of type I collagen mRNAs are present in the cytoplasm of well-differentiated chondrocytes which do not synthesize detectable amounts of type I collagen.…”
Section: T He Onset Of Cartilage Differentiation In the Developingsupporting
confidence: 93%
“…Evidence for the translational regulation of type I collagen gene expression in chondrocytes has also recently been provided by other investigators. Type I collagen mRNAs have been detected in limb and sternal cartilage (22); in the cytoplasm of cultured sternal chondrocytes (31); and in cultured vertebral chondrocytes, which also do not synthesize type I collagen (1,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy, in other conditions in which the levels of procollagen mRNAs are suppressed parallel to suppression of collagen protein synthesis, such as infection with Rous sarcoma virus, the effect is probably exerted at the level of transcription [30,31]. On the other hand, Focht and Adams [32] have recently shown that control of type I collagen gene expression may be exerted at both transcrtptional and posttranscrtptional levels. Of interest is our finding in the synovial cell preparation examined that the ratio of al(I)/cu2(1) procollagen mRNAs was considerably less than 2, the ratio predicted and observed in previous studies utilizing these cDNA probes [20] and confirmed by us in the normal strain of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%